(untitled) (Annual of the Faculty of Philosophy in Skopje, 2016)
This paper analyzes the tides of certain liberal tendencies in the Macedonian society during the period of socialist Yugoslavia. The analysis is set in the context ofpolitical freedoms, freedom of work and opportunities for different interpretations of the social conditions in that time. In this framework some typical examples of a personal nature are suggested through which the trends of Bolshevism and liberalism in the country were violated.